The Role of Wait Time in the Process of Oral Questioning in the Teaching and Learning Process of Mathematics - Mahmud, Muhammad Sofwan (International Journal of Advanced Science and Technology, 2019)
This study was conducted to determine the role played by wait time in the process of oral questioning in mathematics teaching in primary school. This study was a qualitative study using the case study method. Data were collected through semi-structured interviews, document analysis and field notes. Six mathematics teachers from six different primary schools were selected as participants of the study using purposive sampling method. The data were then analyzed using a constant comparative method to identify the patterns and themes that emerged from the data obtained. The study identified that waiting period serves to encourage weak students to also try to answer questions, provide space for students to think, encourage more accurate answers from students, increase the number of students who volunteer to answer questions, maintain student interest and encourage discussion among students. Therefore, all of these roles are seen as helpful in improving students' mathematical learning to a greater degree.